Viral load and antibody boosting following herpes zoster diagnosis - Warren-Gash, Charlotte (J Clin Virol, 2018)
BACKGROUND: Acute varicella zoster virus (VZV) replication in shingles is accompanied by VZV antibody boosting. It is unclear whether persisting virus shedding affects antibody levels. OBJECTIVES: To investigate the relationship between VZV viral load and antibody titres in shingles patients during six months following diagnosis and assess whether VZV antibody titre could discriminate patients with recent shingles from healthy population controls. STUDY DESIGN: A prospective study of 63 patients with active zoster. Blood samples were collected at baseline, one, three and six months to measure VZV DNA and IgG antibody titre. We compared VZV antibody titres of zoster patients and 441 controls. RESULTS: In acute zoster, viral load was highest at baseline and declined gradually over the following six months. Mean antibody titres rose fourfold, peaking at one month and remaining above baseline levels throughout the study. Antibody levels at one, three and six months after zoster were moderately correlated with baseline but not subsequent viral load. Regarding use of antibody titres to identify recent shingles, to achieve 80% sensitivity, specificity would be 23.4%, 67.7%, 64.8% and 52.6%, at baseline, visit 2, 3 and 4 respectively, whilst to achieve 80% specificity, sensitivity would be 28.3%, 66.1%, 52.6%, 38.6%, at baseline, visit 2, 3 and 4 respectively. CONCLUSIONS: Clinical VZV reactivation boosted VZV antibody levels and the level of boosting was dependent upon baseline viral replication. While antibody titres could discriminate patients with shingles 1–6 months earlier from blood donor controls, there was a large trade-off between sensitivity and specificity.